Analysis of Determinants of Organizational Citizenship Behavior of Professional and Non-Professional Staff in North Sumatra Hospitals: Structural Equation Model Approach - Efendi, Efendi; Siregar, Liper; Indajang, Kevin; Nainggolan, Anju Bherna D.; Sudirman, Acai (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
Organizational Citizenship Behavior (OCB) includes voluntary behavior beyond formal duties, considered necessary for increasing organizational effectiveness and efficiency. In the hospital context, these behaviors can significantly impact service quality and patient satisfaction. This study aims to analyze the determinants of Organizational Citizenship Behavior (OCB) among professional and non-professional staff in hospitals in North Sumatra using the Structural Equation Model (SEM) approach. Data was collected through a survey of several professional and non-professional staff in several hospitals in North Sumatra and analyzed using SEM to understand the causal relationship between variables. The results of data analysis confirm that transformational leadership, proactive personality, employee engagement have a positive and significant effect on organizational citizenship behavior. The research results are hoped to provide valuable insights for hospital management in designing strategies to facilitate and increase OCB among employees, thereby supporting overall organizational goals.